The use of small photovoltaic systems for the electrification of off-grid homes - Muller, Donovan Herbert (Energy Research Centre, 2016)
This thesis presents a study of the technical, economic and social appropriateness of small stand-alone photovoltaic (PV) systems for meeting minimal electrical requirements in low-income off-grid households. A comprehensive review of the literature on photovoltaic technology was undertaken to identify key theoretical parameters and issues, and also to determine what the experience has been of similar applications in third world countries. Two PV systems were installed as demonstration projects: one at Uitsig near Cape Town, and the other at Omdraaisvlei in the Northern Cape. In order to monitor and evaluate the techriical performance of these systems, remote data capture units were installed for measuring appropriate parameters for analysis on typical daily, weekly and monthly bases. The degree of matching between the PV output characteristics and the battery and load demand was examined as weLl as the costs of system and component efficiencies under different operating conditions. The economic evaluation aimed to compare small PV systems with these of alternative power systems, for example petrol generators. Using a life cycle costing methodology (discounted to present value) the least-cost option for small power systems was determined under a range of financial scenarios. The social evaluation aimed at determining the impact of PV power on peoples' lifestyles. The results of the two demonstration projects have shown that photovoltaics can appropriately meet small domestic power needs in off-grid applications, providing clean, reliable, maintenance-free electricity which is far more convenient than other electricity producing technologies. Photovoltaics proved to be very much more cost effective than petrol generators, and were also found to be cheaper than coventionally used energy sources such as paraffin, candles and batteries. Both of the demonstration project households were extremely satisfied with the PV systems, which have resulted in significant improvement in quality of lifestyles. However, based on the overall performance of the systems it was recommended that more research was needed, using local conditions, and data to develop better PV system design and sizing methodologies.